Design and development of a low-power motorcycle camshaft copying machine: feasibility and accuracy evaluation - Raynaldi Prima Kurnia Putra; Muhammad Iqbal Prihanto; Sudarwanto (Universitas Negeri Yogyakarta, 2025)
This research aims to design, develop, and evaluate the feasibility and accuracy of a motorcycle camshaft copy machine as an alternative to protect the privacy of modified camshafts from copying or duplication. This research used the ADDIE development model, involving: (1) problem analysis and needs analysis, which then produced a motorcycle camshaft copy machine; (2) the design phase, resulting in a Safety Factor of 1.23 with a load of 22.046 lb force or 10 kg; (3) the development phase, including the process of cutting the frame steel, welding to make the frame, drilling to make holes in the frame steel, assembling the motorcycle camshaft copy machine components, and painting; (4) the implementation phase, consisting of a feasibility test with a result of